IMPLEMENTASI PROGRAM KERJASAMA IPDN DENGAN LEMBAGA DI LUAR NEGERI - Bocut Amarina Malahayati; Budiman Rusli; Candradewini (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The Institute of Domestic Administration as an official higher education institution under the Ministry of Home Affairs plays an important role in implementing and developing civil service higher education. To develop it, it is necessary to cooperate with other institutions as regulated in the Regulation of the Minister of Home Affairs Number 3 of 2008 concerning Government Cooperation with Foreign Parties. Throughout 2018 to 2019 when there was a change in the organizational structure, there was a decrease in participants in cooperation activities with foreign institutions so that the authors were interested in researching how to implement IPDN cooperation with institutions abroad. Referring to the Grindle implementation model and descriptive qualitative research methods, the author uses data collection techniques through interviews and observations. The results showed that the program was implemented according to established procedures, but the magnitude of the leadership intervention, availability of funds and actual issues resulted in changes in participants and collaborative activities.